Perancangan dan Implementasi Aplikasi Internet Billing untuk RT/RW Net pada CV Cipta Semesta Lintas Maya - Muhamad Ibrahim Fajri; Naufal Rifat Aqillah; Khusnul Khotimah; Wasis Haryono (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
The rapid growth of RT/RW Net-based internet services among the community has driven the need for an integrated, efficient, and easy-to-use billing system. The self-help RT/RW Net model often faces challenges in terms of administrative management, especially related to customer recording, billing, and financial reporting which are still done manually. Common problems faced by partners are payment systems that have not been digitized and minimal transparency in data collection and tracking of customer transactions. The purpose of this activity is to design and implement a web-based billing application built using the Laravel framework. This application is designed to facilitate the process of managing customer bills, monitoring internet service usage, and preparing financial reports automatically and in a structured manner. The method of implementing the activity includes the system design stage, training partners in using the application, and assistance in direct implementation in the RT/RW Net operational environment. The results of the activity show that the developed system has succeeded in automating most of the billing process and increasing the efficiency of administrative management by up to 80%. In addition, this system also has a positive impact on increasing transparency and accuracy of customer data. Suggestions for further development include the addition of automatic payment features through integration with payment gateways, as well as improving the user interface to make it more responsive and user-friendly.